Transcriptome Analysis of Bronchoalveolar Lavage Fluid From Children With Mycoplasma pneumoniae Pneumonia Reveals Natural Killer and T Cell-Proliferation Responses - Gao, Man; Wang, Kuo; Yang, Mingyue; Meng, Fanzheng; Lu, Ruihua; Zhuang, Huadong; Cheng, Genhong; Wang, Xiaosong (Frontiers in Immunology, 2018)
Background Mycoplasma pneumoniae pneumonia (MPP) is one of the most common community acquired pneumonia (CAP); this study is to explore the immune-pathogenesis of children MPP. Methods Next generation transcriptome sequencing was performed on the brochoalveolar lavage fluid (BALF) cells from 6 children with MPP and 3 children with foreign body aspiration (FB) as control. Some of the results had been validated by qRT-PCR in an expanded group of children. Results Results revealed 810 differentially expressed genes in MPP group comparing to control group, of which 412 genes including RLTPR, CARD11 and RASAL3 were up-regulated. These up-regulated genes were mainly enriched in mononuclear cell proliferation and signaling biological processes. KEGG pathway analysis revealed that hematopoietic cell linage pathway, natural killer cell mediated cytotoxicity pathway and T cell receptor signaling pathway were significantly up-regulated in MPP children. In addition, significant alternative splicing events were found in GNLY and SLC11A1 genes, which may cause the differential expressions of these genes. Conclusions Our results suggest that NK and CD8+ T cells are over activated and proliferated in MPP children; the up-regulated IFNγ, PRF1, GZMB, FASL and GNLY may play important roles in the pathogenesis of children MPP.